Psychotherapy and the locus of control - Erickson, Richard C. (Journal of religion and health, 1983)
Underlying various actions of both the therapist and the patient are expectations about the measure to which an individual's experiences are the product of powerful external forces or of the person's own actions and decisions. While most of our anthropological theories support the notion that a person's experience is subject to an external locus of control, neither that view nor the opposite emphasizing freedom and autonomy is adequate for the therapeutic enterprise. THere are elements of truth in both positions that ned to be incorporated in therapeutic expectations if the enterprise is to proceed in an orderly fashion.